Preserving the past & engaging the future: theology & religion in American special collections - Graham, M. Patrick (Scholarly editions Librarianship, 2021)
Special collections of religious and theological materials have been part of the landscape of academic libraries in North America from their beginnings. This collection of ten articles treats several aspects of this rich history in three sections: the first deals with the history of specific collections at four libraries; the second treats current attempts to use special collections in teaching and the outreach mission of the library, including the development and use of digital technologies; and the third explores topics related to building library collections for the future, noting both pitfalls to be avoided and intriguing opportunities